Social support and work–family conflict: a systematic literature review of moderating mechanisms across occupational contexts - Febriyeni Febriyeni; Afdal Afdal; Dina Sukma; Nurfarhanah Nurfarhanah (Journal of Counseling, Education and Society, 2026)
Work-family conflict (WFC) remains one of the most widely recognized occupational stressors, contributing to reduced well-being, increased turnover intentions, and poorer physical and mental health among employees. Although previous studies have demonstrated the importance of social support in addressing WFC, a comprehensive understanding of how different forms of support operate across occupations and work contexts is still limited. This systematic review aimed to examine the role of social support in mitigating work-family conflict and its associated outcomes. The review followed the PRISMA 2020 guidelines. A systematic search of the Scopus database using Boolean operators identified 431 articles related to work-family conflict, social support, and organizational support. Following duplicate removal and screening based on predefined inclusion criteria using the PICOS framework, 50 studies published between 2020 and 2026 were selected for analysis. Narrative synthesis revealed four major findings. First, WFC is shaped by occupational and contextual differences, with particularly high levels reported in healthcare, construction, hospitality, and remote or hybrid work settings. Second, organizational and supervisory support consistently reduce the negative effects of WFC by improving job satisfaction, family satisfaction, and overall well-being, thereby lowering emotional exhaustion and turnover intentions. Third, support from spouses and family members strengthens work-life balance and reduces the spillover of work-related stress into family life. Fourth, gender differences remain evident, with women generally experiencing more severe consequences of WFC than men. The findings support the Conservation of Resources Theory and Spillover/Crossover Theory by demonstrating that social support functions as a valuable resource across work and family domains. The review concludes that organizations should combine formal work-family policies with supportive leadership practices to effectively reduce work-family conflict. Future research should emphasize longitudinal designs, cross-cultural comparisons, underrepresented occupations, and the influence of digital and hybrid work environments on work-family dynamics.